The Effect of Customers’ Incivility and Work stress on Job Satisfaction through Burnout - Ribut Prasetyo; Dian Alfia Purwandari; Tantri Yanuar Rahmat Syah (Journal of Economics, Business, and Accountancy Ventura, 2020)
The need for public services is currently increasing both in quantity and quality. In public service, employees need high job satisfaction because if they are satisfied with their work, they will be happy to do their duties and obligations to provide good service. Employee job satisfaction is influenced by several factors both from within and from the environment. This study aimed to examine the effect of customers Incivility and work stress on job satisfaction through burnout. This research was conducted on 191 respondents in the office of the Unit of Investment and One-Stop Services in the Kelurahan in DKI Jakarta Province. The survey was conducted by distributing questionnaires to 191 front office officers working in public service offices. The data were analyzed using the SEM (Structural Equation Modeling) analysis technique using Lisrel. The results of the study found that customers Incivility and work stress have a positive and significant effect on burnout. Furthermore, burnout has a negative and significant effect on job satisfaction. This study implies the importance of local government to pay attention to employee burnout aspects in increasing job satisfaction and front office employee performance.